Alur Laporan Pertanggungjawaban Setelah Kegiatan Workshop Persiapan International Monetary Fund – World Bank Group oleh Kementerian Pariwisata RI - Despriyanti Despriyanti; Sudarno Sudarno (Bisnis Event, 2020)
The execution of the activity report after the event takes place is part of the Post Event stage. Basically an event report is a form of presenting facts about a situation or an activity, the facts presented are related to the responsibilities assigned to the reporter. Activity report or accountability report is an overview of the things implementing the activity that must be delivered by the coach to the party who gave the task as the responsibility of the activities that took place. The Ministry of Tourism held a workshop to educate the public and the Central Bureau of Statistics, that it was important to properly understand how the MICE business in Indonesia and the need for detailed calculations for state revenues obtained from MICE businesses in Indonesia, the workshop can be said as a successful event not only when the event takes place, but there is a Post Event that is very important for the event, namely the making of accountability reports, the accountability report must include all original documents in the form of; Visum, Letter of execution of duties, Statement of responsibility, official travel warrant, list of real expenses, details of official travel expenses, receipts, lodging invoices, electronic tickets, boarding passes, and reports on workshop activities, the accountability report has a path that must be passed, namely; Endorsement from Officials submitting official events and trips. On this occasion the author uses the Methods of Observation Analysis, Interviews, and Documentation.